2016
DOI: 10.4081/aiua.2016.4.320
|View full text |Cite
|
Sign up to set email alerts
|

Testicular sparing surgery in small testis masses: A multinstitutional experience

Abstract: Introduction: The incidence of benign testicular tumors is increasing in particular in small lesion incidentally found at scrotal ultrasonography. Primary aim of this study was to perform radical surgery in malignant tumor. Secondary aim was to verify the efficacy of the diagnostic-therapeutic pathway recently adopted in management of small masses with testis sparing surgery in benign lesions. Materials and methods: In this multicenter study, we reviewed all patients with single testis lesion less than 15 mm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 6 publications
3
26
0
Order By: Relevance
“…In the infertile population, testicular tumors have been reported as 20-fold more frequent than in the general population, due to screening and related disorders identified as risk factors (cryptorchidism, Klinefelter’s syndrome, or gonadal dysgenesis syndrome) (Raman et al , 2005). The recent literature includes several series of small incidental, asymptomatic, non-palpable testicular tumors discovered due to the increase in referrals for scrotal US (Ates et al , 2016; Bozzini et al , 2013; Carmignani et al , 2004; Colpi et al , 2005; De Stefani et al , 2012; Djaladat, 2015; Drudi et al , 2016; Eifler et al , 2008; Galosi et al , 2016; Gentile et al , 2013; Giannarini et al , 2007; Hopps and Goldstein, 2002; Isidori et al , 2014; Lagabrielle et al , 2018; Leroy et al , 2003; Ma et al , 2017; Mancini et al , 2007; Muller et al , 2006; Paffenholz et al , 2018; Powell and Tarter, 2006; Raman et al , 2005; Scandura et al , 2018; Sheynkin et al , 2004; Shilo et al , 2012a; Shilo et al , 2012b). Most of these studies demonstrated a high prevalence of LCTs among nonpalpable masses, with an overall mean prevalence value of 26.6% [18.3–34.9 95% CI] (Table I), in contrast to large palpable testisticular tumors, which are malignant in >90% of cases (Bozzini et al , 2013, Elert et al , 2002; Giannarini et al , 2008; Sheynkin et al , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In the infertile population, testicular tumors have been reported as 20-fold more frequent than in the general population, due to screening and related disorders identified as risk factors (cryptorchidism, Klinefelter’s syndrome, or gonadal dysgenesis syndrome) (Raman et al , 2005). The recent literature includes several series of small incidental, asymptomatic, non-palpable testicular tumors discovered due to the increase in referrals for scrotal US (Ates et al , 2016; Bozzini et al , 2013; Carmignani et al , 2004; Colpi et al , 2005; De Stefani et al , 2012; Djaladat, 2015; Drudi et al , 2016; Eifler et al , 2008; Galosi et al , 2016; Gentile et al , 2013; Giannarini et al , 2007; Hopps and Goldstein, 2002; Isidori et al , 2014; Lagabrielle et al , 2018; Leroy et al , 2003; Ma et al , 2017; Mancini et al , 2007; Muller et al , 2006; Paffenholz et al , 2018; Powell and Tarter, 2006; Raman et al , 2005; Scandura et al , 2018; Sheynkin et al , 2004; Shilo et al , 2012a; Shilo et al , 2012b). Most of these studies demonstrated a high prevalence of LCTs among nonpalpable masses, with an overall mean prevalence value of 26.6% [18.3–34.9 95% CI] (Table I), in contrast to large palpable testisticular tumors, which are malignant in >90% of cases (Bozzini et al , 2013, Elert et al , 2002; Giannarini et al , 2008; Sheynkin et al , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…7 Several previous papers reported even higher incidence of benign pathology (up to 60%) of tumors in testicular masses smaller than 1.5 cm. 7,8 In our study, the mean tumor size was 14.6 mm. Malign lesions were observed in 4 out of 13 patients (30.7%), while benign lesions were observed in 9 out of 13 patients (69.3%), which were compatible with the previous studies.…”
Section: Discussionmentioning
confidence: 55%
“…were able to save testis in 40% of patients presenting with lesions smaller than 15 mm, discovering benign lesions. 12 …”
Section: Discussionmentioning
confidence: 99%